The academic attributes of best human resources needed in creative education - Ab. Aziz Shuaib; Olalere, Folasayo Enoch (2013)
Creative education includes active cognitive processes such as creating, problem-solving, reasoning, decision making and evaluation. However, the process requires appropriate human resources with the right academic attributes to guide the process along, most especially in the upcoming conceptual age where people will no longer live in the sequential, logical and analytical order of information age but rather a nonlinear, intuitive and holistic world. Therefore, this paper seeks the knowledge regarding the type of brain require in conceptual age, illuminates on the attributes of best academicians required in creative education. It also proposed the learning and teaching method that academicians in creative education can use in teaching and learning process.